NUMERIC RATING SCALE ANALYSIS OF TRIGEMINAL NEURALGIA PATIENTS BEFORE AND AFTER MICROVASCULAR DECOMPRESSION - Fitri Amelia, Elena Ghentilis; Turchan, Agus; Rehatta, Nancy Margarita; Hidayati, Hanik Badriyah (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Trigeminal Neuralgia is a common condition of facial pain and its significantly affect patients’ daily life. Microvascular decompression is one of the interventional pain management for trigeminal neuralgia. There is still a little data obtained on evaluation of facial pain after microvascular decompression in Indonesia. Objective: This research aimed to evaluate facial pain after microvascular decompression of trigeminal neuralgia patients in Dr. Soetomo General Hospital, PHC Hospital, and Bangil General Hospital, Indonesia.Methods: The research design was a pretest-posttest with total sampling. Data were obtained from medical records from January 2018 until June 2019. Researches used Numeric Rating Scale (NRS) as pain measurement. The data obtained were analyzed by descriptive statistical test, normality test, and paired t-test.Results: Trigeminal Neuralgia patients that has been treated with microvascular decompression have an average facial reduction from 7.33±2.29 to 1.89±3.41 with p = 0.001. This result showed that the microvascular decompression has significantly reduce facial pain in patients with trigeminal neuralgia.Conclusion: Microvascular decompression significantly reduce the facial pain of trigeminal neuralgia patients.